Answer:
y = (-1/2)x + 1/2
Explanation:
Thank you for sharing the work you've already done! If we solve -6x+3y=6 for 3y, by adding 6x to both sides, we get 3y = 6x + 6, or (solving for y)
y = 2x + 2. Compare this to your work.
If this given line -6x+3y=6 has the slope m = 2, then any line perpendicular to it has the slope -1/2, the negative reciprocal of 2.
Now, knowing this new slope and the fact that (2, 0) lines on a line perpendicular to -6x+3y=6, we use the slope-intercept formula, with m = -1/2, y = 0 and x = 2:
That formula, y = mx + b, becomes 0 = -1/2 + b. Thus, b = 1/2, and the desired equation is
y = (-1/2)x + 1/2.